SenseCam and memory rehabilitation - Berry, Emma; Browne, Georgina; Hodges, Steve; Smyth, Gavin; Kapur, Narinder; Williams, Lyndsay; Butler, Alex; Woodberry, Ken (Microsoft Research, 2007)
SenseCam and memory rehabilitation slideshow.
Presentation at the 4th Satellite Symposium on Neuropsychological Rehabilitation, San Sebastian, July 2007